Exploring Learner Autonomy through Technology-Integrated Strategies in EFL Classrooms: A Systematic Review - Putra, M.R.; Authar, N.; Saputri, T.; Djuwari, Djuwari; Zaniar, S. (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to systematically review various technology-integrated strategies used to support learner autonomy in English as a Foreign Language (EFL) classrooms. Using a qualitative systematic review approach, 15 articles published between 2013 and 2025 were analyzed to identify the types of technology, learning strategies, and dimensions of autonomy promoted. The findings show that technologies such as mobile applications, learning management systems (LMS), and artificial intelligence can foster cognitive, metacognitive, behavioral, and affective dimensions of learner autonomy. These results emphasize the importance of intentional pedagogical design and the teacher’s role in facilitating technology integration to create autonomous learning environments. The implications of this review highlight the need for teacher training, policy support, and the development of adaptive learning strategies suited to learners’ needs and contexts. Furthermore, the review reveals that effective integration of technology requires alignment between instructional goals, digital tools, and learner characteristics. Teachers play a crucial role in scaffolding students’ ability to plan, monitor, and evaluate their own learning processes. In addition, interactive platforms and personalized feedback mechanisms provided by digital tools enhance learners’ motivation and engagement. However, challenges such as unequal access to technology, limited digital literacy, and insufficient institutional support may hinder implementation. Therefore, stakeholders should prioritize inclusive policies and continuous professional development to maximize the benefits of technology-enhanced learning. Future research is recommended to explore longitudinal impacts and diverse educational contexts to further validate these findings and inform best practices in promoting learner autonomy across different proficiency levels and sociocultural backgrounds of EFL learners worldwide